Re‐Claiming Disability: Identity, Procedural Justice, and the Disability Determination Process. Issue 1 (17th February 2016) - Dorfman, Doron
Abstract : This research highlights the crucial role of an intimate link between a disabled person's self‐identity and the perceived fairness of legal procedures. In doing so, it brings to the foreground a wholly ignored aspect of procedural justice. Earlier researchers have failed to delve into the role identity politics plays in the relationship between the institutions and the beneficiaries of their services, and the way different members of a group understand and define themselves. This research explores the way people with disabilities in the United States, with different kinds of disability identities, experience and evaluate the procedure of claiming Social Security benefits. The findings suggest that disabled people who identified with the social model of disability (as opposed to the medical‐individual models) hold a critical view of the procedure for retaining benefits. They felt they had no control over it, could not voice their opinions, were mistreated by representatives, and had to present an image that was not necessarily true of their disability. They also saw the procedure as discouraging them from participating fully in the labor market, and consequently integrating better in society, an idea that was not present among disabled people who identify with medical‐individual models. Exposing this relationship between the way people perceive themselves and the way they experience and evaluate legal procedures can contribute to the creation of better policies, while improving communication between the state and members of the disability community, along with other marginalized groups.